THE PROCESS OF INTRODUCING THE ORGANIZATION’S NEW PRODUCT TO THE MARKET - DANYLIUK, Viacheslav; YATSYSHYNA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In today’s conditions of dynamic development of market relations and growing competition, innovative activity becomes a key success factor for any organization. One of the most important aspects of this activity is bringing new products to the market that can meet the changing needs of consumers and ensure sustainable growth of the organization. Defining the concept of "new product" is an important step in understanding this process and its role in the overall strategy of the organization’s development. A new product can have different forms and characteristics, depending on the industry in which it is created and the specifics of the market to which it is introduced. These can be both completely new products or services, and improved versions of existing products that offer consumers new functionality or improved design. It is important to understand that the novelty of a product can be relative and depend on consumer perception and the competitive environment. Bringing a new product to market is not only an important strategic step for an organization, but also a complex process involving numerous managerial aspects. This process requires careful planning, coordination and integration of various functional units of the organization. Successful management of the introduction of a new product is determined by the organization’s ability to ensure harmonious interaction between development, marketing, production, as well as constant monitoring of market conditions and consumer expectations. The introduction of a new product to the market is considered by the global organization management system as the main business process. This includes not only the development of a new product, but also the adaptation of existing processes, structure and resources. A change to one of the warehouse processes, for example, to the owner of process, can lead to significant transformations that will affect the entire organization.